DESIGN OF FUNCTIONAL CLOTHING FOR PATIENTS OF HOSPITAL TAKING INTO ACCOUNT THE CONDITIONS OF ITS OPERATION - Колосніченко, О. В.; Пашкевич, К. Л.; Остапенко, Н. В.; Люклян, Н. Р.; Колосніченко, М. В. (Art and Design, 2023)
Purpose: to establish the basic principles of the development of modern functional clothing for patients, taking into account the peculiarities of its operation. Methodology. The theoretical method, including analysis, synthesis and analogy, is applied; method of system analysis. Results. The characteristics of the patient's movement modes are given: general, ward, semi-bed, bed rest, strictly bed rest. The characteristic movements of the patients were analyzed taking into account the mode of activity. Based on the Protocols of a nurse (paramedic, midwife) for patient care and the performance of basic medical procedures and manipulations, the main medical procedures in which there is contact with clothing were analyzed, the topography of the areas of medical procedures and the topography of the areas of physical, psychophysical, chemical, and biological influence were formed. factors. Recommendations are provided for constructive and technological solutions when designing clothes for patients depending on the movement mode. Scientific novelty. Groups of patients are specified according to their activity regimes. The direction of functional and constructive design of clothing, which is based on the systematization of characteristic movements, positions of patients and topographies of medical procedures, has been improved. The practical significance. Based on the study and analysis of characteristic movements, positions of patients and the conduct of medical procedures, recommendations were formed regarding constructive and technological solutions for the design of shoulder and lumbar products for patients depending on the movement mode.